QUY TRÌNH XÁC ĐỊNH SELEN TRONG MẪU SỮA BẰNG QUANG PHỔ HẤP THỤ NGUYÊN TỬ SỬ DỤNG KỸ THUẬT HIDRUA HÓA (HG-AAS) - Lê, Bảo Hưng; Nguyễn, Kim Thuỳ; Nguyễn, Thị Thu Lý; Nguyễn, Thị Thu Hằng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE PROCESS OF DETERMINING SELENIUM IN MILK BY ATOMIC ABSORPTION SPECTROMETRY USING HYDRIDE GENERATION TECHNIQUE (HG-AAS)This article shows the process of quantifying selenium by atomic absorption spectrometry using hydride generation technique (HG-AAS) for milk samples. It was found that in the process, the optimized conditions to form H2Se are the most important to ensure reliable results. In the method Se (VI) is reduced to Se (IV) with 6N HCl. It also presents the reaction conditions to form H2Se (0,5% NaBH4 and 8N HCl; the velocity of acid and reductant to gas/liquid separator of 0.9 ml/min) and the most suitable samples digestion mixture (HNO3:H2O2 with volume ratio of 9:3). The resulting procedure has high accuracy, sensitivity and repeatability (%RSD < 11%, the recovery of selenium is from 88,0 to 91,8 %, LOD is 0.4 ppb), and being proposed to analyse selenium in real milk samples.